2015
DOI: 10.1186/s12884-015-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Progression from gestational diabetes to type 2 diabetes in one region of Scotland: an observational follow-up study

Abstract: BackgroundThe aim of this study was to investigate long-term risk of type 2 diabetes (T2D) following a diagnosis of gestational diabetes and to identify factors that were associated with increased risk of T2D.MethodsAn observational cohort design was used, following up all women diagnosed with gestational diabetes mellitus (GDM) attending a Diabetes Antenatal Clinic in the Dundee and Angus region of Scotland between 1994 and 2004 for a subsequent diagnosis of T2D, as recorded on SCI-DC (a comprehensive diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
2
35
3
Order By: Relevance
“…In all, there were 22 prospective cohort studies (56%) [ 13 , 14 , 17 , 19 21 , 29 , 32 , 35 – 37 , 39 – 41 , 43 , 44 , 46 – 48 , 50 , 52 , 55 ] and 17 retrospective cohort studies (44%) [ 15 , 27 , 28 , 30 , 31 , 33 , 34 , 38 , 42 , 45 , 49 , 51 , 53 , 54 , 56 58 ]. The studies evaluated the association of maternal characteristics, pregnancy-specific factors and postpartum characteristics with progression to type 2 diabetes in women with GDM.…”
Section: Resultsmentioning
confidence: 99%
“…In all, there were 22 prospective cohort studies (56%) [ 13 , 14 , 17 , 19 21 , 29 , 32 , 35 – 37 , 39 – 41 , 43 , 44 , 46 – 48 , 50 , 52 , 55 ] and 17 retrospective cohort studies (44%) [ 15 , 27 , 28 , 30 , 31 , 33 , 34 , 38 , 42 , 45 , 49 , 51 , 53 , 54 , 56 58 ]. The studies evaluated the association of maternal characteristics, pregnancy-specific factors and postpartum characteristics with progression to type 2 diabetes in women with GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Feig et al reported maternal age as an independent predictor of developing diabetes in a large population based study in Canada [18]. In contrast, two studies conducted in South India and Scotland did not show a statistically significant association between maternal age and development of T2DM [21, 32]…”
Section: Discussionmentioning
confidence: 99%
“…GDM is known to increase short-and long-term cardio-metabolic risk especially for type 2 diabetes [6,7,10]. A third of the GDM cases in our study was persistently hyperglycemic at 12 weeks postpartum.…”
Section: Discussionmentioning
confidence: 53%
“…Adverse outcomes linked to GDM include preeclampsia, postpartum hemorrhage, obstructed labor, cesarean delivery, macrosomia, birth trauma, asphyxia, neonatal hypoglycemia and perinatal mortality [5,8,9]. GDM affects breastfeeding [7] and long-term cardio-metabolism of mother-offspring pairs [6,7,10]. Despite recommendation by the International Association of Diabetes and Pregnancy Study Group (IADPSG) on 'one-step' testing of all pregnant women using fasting glucose and the 'gold standard' 2-hour oral glucose tolerance test (OGTT) [11], disagreements exist on diagnostic thresholds [12].…”
Section: Methods and Findingsmentioning
confidence: 99%